PEMBERDAYAAN IBU RUMAH TANGGA MELALUI PENERAPAN HOME BASED FOOD WASTE MANAGEMENT MENUJU DAPUR BERKELANJUTAN - Riska Mayangsari; Justiyulfah Syah; Andi Sri Rahayu Kasma (Universitas Mataram, 2026)
Stunting remains one of the most complex nutritional problems, influenced not only by dietary patterns and nutrient intake but also by poor environmental sanitation. One of the indirect causes of sanitation problems is the suboptimal management of household waste, particularly food waste, which accumulates and poses a risk of environmental contamination. Improper food waste management can increase the potential for disease transmission and worsen environmental conditions. This activity aimed to improve participants’ knowledge and skills in reducing household waste through the efficient implementation of food preparation and meal preparation concepts, as well as the utilization of food residues for composting. The methods included socialization, education, and direct simulation of compost production using a participatory approach, enabling participants to understand and apply waste management practices independently and sustainably. The results showed an increase of 70–80% in participants’ knowledge regarding food waste management and sustainable kitchen practices. This community service activity promotes the creation of environmentally friendly sustainable kitchens and is expected to contribute to improving household sanitation and preventing stunting in the community.